2014
DOI: 10.7482/0003-9438-57-018
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical parameters in the blood of an indigenous Croatian breed – Istrian cattle

Abstract: Abstract. Haematological and biochemical parameters were examined in the blood of 87 cows, bulls and oxen of the indigenous Croatian breed, Istrian cattle. The sample represents 11.93 % of the total adult population. This breed is classified as highly endangered. The age of tested animals was between 2 and 17 years. Cattle were divided into three groups, animals aged 2 to 6 years (n=19), 7 to 10 years (n=37), and older than 10 years (n=31). Animals were kept in the area of Istria County, mostly in stables thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
2
3
0
Order By: Relevance
“…In the present study, TLC and number of lymphocytes decreased where as neutrophil and eosinophilic counts increased with ageing, mild neutrophilia are predominant in 8 to 10 year and above 10 year age group cattle, which is similar to ndings of Bedenicki et al (2014). Reduced lymphocyte count may be one of the causes of immunosenescence.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, TLC and number of lymphocytes decreased where as neutrophil and eosinophilic counts increased with ageing, mild neutrophilia are predominant in 8 to 10 year and above 10 year age group cattle, which is similar to ndings of Bedenicki et al (2014). Reduced lymphocyte count may be one of the causes of immunosenescence.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been reported in Queensland, Australia, in Holstein-Friesian cows before and after calving, and the values were lower for RBC and HGB (Jonsson et al 2013). However, Bedenicki et al (2014) reported a high HCT in the Croatian breed. In general, beef cattle breeds have higher RBC values than dairy cattle.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, in this study, the number of RBC differs from the values reported by other authors. Lower values of RBC and HGB (6-7 x 10 3 mL and 10.0 to 10.7g/dL) where found in the study carried out by Bedenicki et al (2014), who sampled lactating cows of the Croatian Istria autochthonous breed. Similar results have been reported in Queensland, Australia, in Holstein-Friesian cows before and after calving, and the values were lower for RBC and HGB (Jonsson et al 2013).…”
Section: Discussionmentioning
confidence: 78%
“…This study showed that AST (142.56±20.55 U/l) was slightly higher in female compared to the male (137.00±16.24 U/l), while level of ALT/SGPT were 46.44±10.99 U/l in male and 46.41±10.23 U/l in female. Although, the result was not significant (p>0.05), level of AST and ALT in SO cattle was higher compared to standard (Bedenicki et al 2014). Standard level of AST and ALT is 60-125 U/l and 6.9-35 U/l, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 66%